Analisis Biaya Produksi, Tingkat Penjualan dan Laba (Studi Kasus Pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Tahun 2022 dan 2023) - Kertarajasa, Astroyudha; Annisa, Mutiara Lusiana; Hadiwijaya, Hendra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze production costs, sales levels and profits in food and beverage companies listed on the Indonesia Stock Exchange (BEI) in 2022 and 2023. The data used in this research is data for 2022 and 2023 from the BEI. Data analysis uses quantitative descriptive analysis to determine production costs, sales levels and profits. The research sample consisted of 21 food and beverage companies listed on the Indonesia Stock Exchange. In 2022, the Budi Starch & Sweetener Tbk company will have the highest production cost to sales ratio among food and beverage companies listed on the IDX, namely 0.95. In contrast, the company Multi Bintang Indonesia Tbk has the lowest ratio of 0.35. In 2023, the Bumi Teknokultura Unggul Tbk company recorded the highest production cost to sales ratio of 1.020. In contrast, the company Multi Bintang Indonesia Tbk has the lowest ratio with a value of 0.390. The company Akasha Wira International Tbk recorded a high profit to sales ratio of 0.28. In contrast, the company Bumi Teknokultura Unggul Tbk experienced a decrease in its profit to sales ratio to 0.86. The Prasidha Anega Niaga Tbk company recorded an increase in the profit to sales ratio of 0.53. In contrast, the company Bumi Teknokultura Unggul Tbk experienced a decrease in its profit to sales ratio to 0.57